IMPLEMENTATION OF WOMEN COMPONENT PLAN IN RURAL GOVERNANCE: GLIMPSES OF A RISING TREND - K. GIREESAN & JOS CHATHUKULAM (Samyukta: A Journal of Women’s Studies, 2009)
n this paper, an attempt has been made to analyse the implementation of WCP in the local government institutions of a Block Panchayat in Thrissur District during the Kerala Development Programme (KDP). The need for taking up an overall review regarding the implementation of WCP in the State has been highlighted. The study views that the pattern of expenditure on projects directly benefiting women is less when compared to all the categories. It is viewed that the possibility of various operational issues inimical to women in the society has been the major hurdle for incorporating gender needs into the planning process of the local government institutions. There is a strong need for initiating and sustaining the efforts made by women’s organizations and social activists for implementing WCP. The need for taking up a macro study in the State to review the implementation of WCP during the last decade is also highlighted here.